3D hydrogel stem cell niche controlled by host-guest interaction affects stem cell fate and survival rate. (October 2019) - Hong, Ki Hyun; Song, Soo-Chang
Abstract: Host-guest interaction using β-cyclodextrin (β-CD) and adamantane (Ad) allows facile modulation of guest molecule concentration in 3D hydrogels. Based on this phenomenon, we prepared a thermosensitive poly(organophosphazene) bearing β-CD hydrogel (β-CD PPZ, as host) and Ad-Arg-Gly-Asp (Ad-RGD, as guest). The structures of synthesized thermosensitive β-CD PPZ and Ad-RGD were confirmed by 1 H NMR and FT-IR. The β-CD PPZ/Ad-RGD mixture was prepared by simple mixing and elicited thermosensitive properties with the formation of gelation in all Ad-RGDs mixing proportions at the body temperature. Strong and controlled host-guest interactions between β-CD PPZ and Ad-RGD were observed in 2D-NOESY, DLS, and TEM. Regulated MSC behaviors were elicited based on the use of controlled Ad-RGD amounts at the level of in vitro and in vivo. As the amount of Ad-RGD was increased in the β-CD PPZ hydrogel, MSC survival rate was enhanced and was prone to express osteogenic factors. While Ad-RGD is absent or low in hydrogel, relatively poor MSC survival rate and adipogenesis were exhibited. Altogether, we verified that survival rate and differentiation of MSCs could be controlled by host-guest interaction system with thermosensitive 3D hydrogel. This proposed 3D hydrogel controlling system with host-guest interaction is expected to be a platform technology as changing guest molecules.